"Alternated cooling and heating" strategy enables rapid fabrication of highly-crystalline g-C3N4 nanosheets for efficient photocatalytic water purification under visible light irradiation. (October 2018) - Kang, Shifei; Zhang, Lu; He, Maofen; Zheng, Yuanyi; Cui, Lifeng; Sun, Di; Hu, Bing
Abstract: Highly-crystalline 2-dimensional (2D) graphitic carbon nitride (g-C3 N4 ) nanosheets with low structural imperfection usually possess high photocatalytic activity that benefits from the suppressed electron–hole recombination. However, the conventional exfoliation strategy is incapable for fast and clean preparation of such highly-quality g-C3 N4 nanosheets from their bulk-type counterparts. Herein, highly-crystalline few-layer g-C3 N4 nanosheets were synthesized only within 10 min by judiciously combining flash freezing and microwave-assisted thermo-exfoliation. Physicochemical characterization showed the ultrathin g-C3 N4 nanosheets had high crystallinity, narrowed band gap (2.62 eV), enlarged specific surface area (88.59 m 2 /g) and enhanced electron transport ability. The quasi-2D few-layer g-C3 N4 nanosheets were more efficient than bulk g-C3 N4 in photocatalytic water purification and disinfection, as evidenced by 3-fold enhancement in humic acid photodegradation and fast water disinfection against Escherichia coli under visible-light irradiation. Such improvements were mainly attributed to the reduction of structural defects and enrichment of exposed active sites, which together led to efficient self-suppression of electron–hole recombination. These findings provide an inspiration for scale-up and clean production of highly-active 2D materials towards environmental and biological application. Graphical abstract: Image 1